2007
DOI: 10.1002/casp.913
|View full text |Cite
|
Sign up to set email alerts
|

Mental health teaching to UK psychology undergraduates: report of a survey

Abstract: One of the limitations on developing more progressive applied psychology training is the teaching received by students at undergraduate level. In this study, we focus on the provision of teaching about mental health or its equivalents (e.g. abnormal psychology and clinical psychology) on UK undergraduate psychology programmes. Most students who go on to train as clinical psychologists will have received teaching on modules like these. A survey questionnaire was sent to 109 university departments which might of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…In a survey of university departments offering mental health modules to psychology undergraduates in the UK, 50% of the respondents indicated that greater input from consumers would be valuable to improving their courses (Cromby et al . ). When the survey was undertaken, only two of the 66 psychology programs (3%) involved consumers as guest speakers.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In a survey of university departments offering mental health modules to psychology undergraduates in the UK, 50% of the respondents indicated that greater input from consumers would be valuable to improving their courses (Cromby et al . ). When the survey was undertaken, only two of the 66 psychology programs (3%) involved consumers as guest speakers.…”
Section: Resultsmentioning
confidence: 97%
“…In a study of undergraduate psychology programs in the UK (Cromby et al . ), only two of the 66 programs included mental health consumers as guest speakers. In psychiatry, 23 of 90 (26%) trainees in the Babu et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…John Cromby, Paula Reavey and I conducted a survey of ‘abnormal psychology’ courses in undergraduate psychology programmes in the UK with some funding from the Higher Education Academy Psychology Network. We found that, although many teachers wanted to cover alternatives to diagnosis, most of the textbooks were entirely structured by them (Cromby et al, 2008). We decided to make a modest intervention and produce a textbook that attempted to develop a consistently psychological approach rather than one predicated on psychiatric diagnosis – Psychology, Mental Health and Distress, published by Palgrave MacMillan (Cromby et al, 2013).…”
Section: Addressing Institutional Interests and Social Functionsmentioning
confidence: 99%
“…GPs provided 86% of these prescriptions and many (58.3% or 12 million) were for antidepressant medications (Australian Institute of Health and Welfare 2008). As one in five Australians now has a diagnosable mental illness there are fundamental problems with health care interventions that continue to focus on the medical model framework of deficit and dysfunction (Cromby et al. 2007) that facilitates the use of medication as the main treatment intervention.…”
Section: The Mental Health Care Challenges For Nurses In the 21st Cenmentioning
confidence: 99%